Public health impact and economic benefits of quadrivalent influenza vaccine in Latin America. Issue 4 (3rd April 2017) - Jamotte, Aurélien; Clay, Emilie; Macabeo, Bérengère; Caicedo, Andrès; Lopez, Juan Guillermo; Bricks, Lucia; Romero Prada, Martín; Marrugo, Rubén; Alfonso, Pamela; Moreno Arévalo, Brechla; Franco, Danilo; Garcia Diaz, Lourdes; et al.
ABSTRACT: Annual trivalent influenza vaccines (TIV) containing 2 A strains and one B lineage have been recommended for the prevention of influenza in most of Latin American countries. However, the circulation of 2 B lineages (Victoria and Yamagata) and difficulties in predicting the predominating lineage have led to the development of quadrivalent influenza vaccines (QIV), including both B lineages. Thus, the objective was to estimate the public health impact and influenza-related costs if QIV would have been used instead of TIV in 3 Latin American countries. We used a static model over the seasons 2010–2014 in Brazil, 2007–2014 in Colombia and 2006–2014 in Panama, focusing on population groups targeted by local vaccination recommendations: young children, adults with risk factors and the elderly. In Brazil, between 2010 and 2014, using QIV instead of TIV would have avoided US$ 6, 200 per 100, 000 person-years in societal costs, based on 168 influenza cases, 89 consultations, 3.2 hospitalizations and 0.38 deaths per 100, 000 person-years. In Colombia and Panama, these would have ranged from US$ 1, 000 to 12, 700 (based on 34 cases, 13–25 consultations, 0.6–8.9 hospitalizations and 0.04–1.74 deaths) and from US$ 3, 000 to 33, 700 (based on 113 cases, 55–82 consultations, 0.5–27.8 hospitalizations and 0.08–6.87 deaths) per 100, 000 person-years, respectively. Overall, the broader protection offered by QIV would have reduced the influenza humanistic and economic burden in the 3 countries. Despite the lack of local data leading to several extrapolations, this study is the first to give quantitative estimates of the potential benefits of QIV in Latin America.